2022
DOI: 10.1172/jci.insight.157285
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage secretory IL-1β promotes docetaxel resistance in head and neck squamous carcinoma via SOD2/CAT-ICAM1 signaling

Abstract: Docetaxel (DTX) combined with cisplatin and 5-FU has been used as induction chemotherapy for head and neck squamous cell carcinoma (HNSCC). However, the development of acquired resistance remains a major obstacle to treatment response. Tumor-associated macrophages are associated with chemotherapeutic resistance. In the present study, increased infiltration of macrophages into the tumor microenvironment was significantly associated with shorter overall survival and increased resistance to chemotherapeutic drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…In this regard, TNF-α may contribute to tumor progression by acting together with TGF-β to induce endothelial-to-mesenchymal transition [30]. IL-1β is involved in regulating epithelialmesenchymal transition, metastasis [31], and chemotherapy resistance [32]. IL-6 promotes the activation of the STAT3 pathway, thereby promoting tumor cell proliferation [33].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, TNF-α may contribute to tumor progression by acting together with TGF-β to induce endothelial-to-mesenchymal transition [30]. IL-1β is involved in regulating epithelialmesenchymal transition, metastasis [31], and chemotherapy resistance [32]. IL-6 promotes the activation of the STAT3 pathway, thereby promoting tumor cell proliferation [33].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Jinushi et al [ 27 ] reported that milk fat globule-epidermal growth factor-VIII (MFG-E8) secreted from TAMs activated STAT3 and Sonic Hedgehog signaling in cancer stem cells, limiting their sensitivity to cisplatin in mice. Macrophage-derived interleukin-1β (IL-1β) upregulated intercellular adhesion molecule 1 (ICAM1) expression on tumor cells to promote their stemness, endowing the chemoresistant property of head and neck squamous cell carcinoma [ 28 ].…”
Section: Macrophages and Therapeutic Resistance In Cancermentioning
confidence: 99%
“…Upon ICAM1 activation, mesenchymal markers such as fibronectin, N-cadherin, and vimentin were observed to be elevated whereas, epithelial marker (E-cadherin) was suppressed, reinforcing the increased EMT features. Further, the IL-1β-SOD2/CAT-ICAM1 pathway is exemplified to contribute to chemoresistance towards docetaxel ( 136 ). TAM markers, CD68 and CD163 were highly expressed in OSCC samples in comparison to normal oral mucosa and dysplastic cell samples.…”
Section: Extrinsic Factors Governing Oscc Stemnessmentioning
confidence: 99%